Macromol. Chem. Phys. 2/2017. Issue 2 (January 2017) - Yuan, Hao; Ma, Qingming; Song, Yang; Tang, Matthew Y. H.; Chan, Yau Kei; Shum, Ho Cheung
Abstract : Back Cover : Janus droplets are fabricated by inducing phase separation in droplets consisting of an aqueous two‐phase system (ATPS). The use of biocompatible ATPS in fabricating the Janus droplets makes them suitable for encapsulating enzymes and cells without significantly compromising their biological activities. The affinity partitioning of the encapsulated ingredients to different ATPS phases facilitates their spontaneous migration into different compartments of the Janus droplets. This is reported by Hao Yuan, Qingming Ma, Yang Song, Matthew Y. H. Tang, Yau Kei Chan, and Ho Cheung Shum* in article number 1600422.